Epididymal sperm reserve in the indigenous pigs (Sus vittatus) of Assam - GOSWAMI, B K; DEKA, B C; BISWAS, R K (The Indian Journal of Animal Reproduction, 2023)
Twenty-seven indigenous pigs of Assam 4 to 12 months of age were used to study the sperm reserve in the caput, corpus and cauda epididymis. The epididymis after castration was separated from the testes and divided into caput, corpus and cauda regions. The spermatozoa from each region of the epididymis was obtained by homogenizing and filtering the homogenate. The sperm concentration in the filtrate was determined by direct haemocytometer method. The distribution of sperm (x 109) in caput, corpus and cauda was 1.02 ± 0.08 ( 17 .20% ), 0.71± 0.05 (11.97%) and 4.19 ±0.21 (70.66%), respectively at 4 months of age which increased to 5.63 ± 0.20 (17.09%), 3.37± 0.03 (10.23%) and 23.95± 0.6] (72.69%), respectively at 12 months of age. The epididymal sperm reserve increased significantly (P<0.01) with advancement in age. The sperm reserve differed significantly (P<0.0 l) between regions of the epididymis, being significantly (P<0.05) higher in cauda than in caput and corpus epididymis. The epididymal sperm reserve had positive significant (P<0.01) correlation with.age (0.98), body weight (0.96), and weights of epididymis (0.97) and testis (0.98).